Epidemiology of spinal column injuries before, during, and after the Covid-19 pandemic – is there any difference? - Zagorac, Slavisa; Vasic, Milos; Novakovic, Uros; Mladenovic, Milos; Tulic, Ivan; Teodosic, Valerija (Medical Research, 2024)
IntroductionThe lack of information in international literature regarding the impact of the introduction and the subsequent termination of epidemiological restrictions during the COVID-19 pandemic on the epidemiology of spinal injuries has led to the constant monitoring and recording of all relevant data on patients with spinal column injuries since the beginning of the pandemic.Study AimTo analyze and compare epidemiological data on patients with spinal column injuries treated at a tertiary healthcare facility in Serbia, before, during, and after the COVID-19 pandemic. Materials and methods This is an retrospective study spanning over three observation periods analyzing patients with spinal column injuries.ResultsThe average age of patients in the first observation period was 47 years; it was 68 years in the second, and in the third it was 39 years. In the first two observation periods, the dominant mechanism of injury was same-level fall, and most of the patients were treated conservatively. When comparing the data on the three groups of respondents, statistically significant differences in the age of the patients and the mechanism of injury can be observed.ConclusionThe COVID-19 pandemic contributed to spinal column injuries being more common among the elderly, due to falls occurring at home. However, after people returned to an active lifestyle, which was especially true of the younger population, there was a sudden increase in the number of spinal column injuries due to road traffic accidents, while due to the frequent occurrence of spinal cord injuries, there was also an increase in the number of emergency surgeries.
Keywords: COVID-19, spinal column injuries, mechanism of injury, surgical treatment